Association of tamoxifen with meningioma: a population-based study in Sweden - Ji, Jianguang (Eur J Cancer Prev, 2016)
Previous studies suggest that hormone therapy may play an important role in the development of meningioma. However, it is unclear whether medication with tamoxifen can prevent meningioma. Our study cohort included all women who were diagnosed with breast cancer between 1961 and 2010, and a total of 227 535 women were identified with breast cancer with a median age at diagnosis of 63 years. Women diagnosed with breast cancer after 1987 were defined as tamoxifen exposed; those diagnosed with breast cancer before or during 1987 were defined as not exposed to tamoxifen. Standardized incidence ratios (SIRs) were used to calculate the risk of subsequent meningioma. Of these women, 223 developed meningioma. For women without tamoxifen exposure, the risk of meningioma was significantly increased, with an SIR of 1.54 (95% confidence interval 1.30–1.81); the risk was not increased in those with tamoxifen exposure (SIR=1.06, 95% confidence interval 0.84–1.32). The increased risk of meningioma in women without tamoxifen exposure persisted during 10 years of follow-up. In this historical cohort study, we found that women diagnosed with breast cancer but not treated with tamoxifen had an increased incidence of meningioma, whereas the incidence was close to that of the general population in patients treated with tamoxifen. This suggests that tamoxifen may prevent the development of meningioma.